Vulvar syringomas: case report - Mendoza Mendoza, Andy Manuel (2021)
Syringomas are benign adnexal tumors rarely reported at the vulvar area. A case is reported and a literature review is performed for the presentation of a 33-year-old woman with multiple papular lesions in labia majora, of long standing, with anatomopathologic diagnosis and treatment by surgical excision under sedation and CO2 laser vaporization.